Associations of short‐ and long‐term mortality with admission blood pressure in Chinese patients with different heart failure subtypes. Issue 12 (2nd November 2022) - Chen, Shilan; Liang, Weihao; Wu, Yuzhong; Chen, Xuwei; He, Xin; Zhao, Jingjing; He, Jiangui; Dong, Yugang; Staessen, Jan A.; Liu, Chen; Wei, Fang‐Fei
Abstract: It remains unknown whether systolic (SBP) and diastolic (DBP) pressure on admission are associated with short‐ and long‐term mortality in Chinese patients with heart failure with preserved (HFpEF), mildly reduced (HFmrEF), and reduced (HFrEF) ejection fraction. In 2706 HF patients (39.1% women; mean age, 68.8 years), we assessed the risk of 30‐day, 1‐year, and long‐term (> 1 year) mortality with 1‐SD increment in SBP and DBP, using multivariable logistic and Cox regression, respectively. During a median follow‐up of 4.1 years, 1341 patients died. The 30‐day, 1‐year, and long‐term mortality were 3.5%, 16.7%, and 39.4%, respectively. In multivariable‐adjusted analyses additionally accounted for DBP or SBP, a higher SBP conferred a higher risk of long‐term mortality (hazard ratio, 1.11; 95% CI, 1.02‐1.22; p = .017) and a lower DBP was associated with a higher risk of all types of mortality ( p ≤ .011) in all HF patients. Independent of potential confounders including DBP or SBP, in patients with HFpEF, higher SBP and lower DBP levels predicted a higher risk of long‐term mortality with hazard ratios amounting to 1.16 (95% CI, 1.04–1.29; p = .007) and .89 (95% CI, .80–.99; p = .028), respectively. In patients with HFmrEF and HFrEF, irrespective of adjustments of potential confounders, DBP was associated with 1‐year mortality with odds ratios ranging from .49 to .62 ( p ≤ .006). In conclusion, lower DBP and higher SBP levels on admission were associated with a higher risk of different types of all‐cause mortality in Chinese patients with different HF subtypes. Our observations highlight that admission BP may help to improve risk stratification.